Assembly of histidine-rich protein materials controlled through divalent cations. (1st January 2019) - López-Laguna, Hèctor; Unzueta, Ugutz; Conchillo-Solé, Oscar; Sánchez-Chardi, Alejandro; Pesarrodona, Mireia; Cano-Garrido, Olivia; Voltà, Eric; Sánchez-García, Laura; Serna, Naroa; Saccardo, Paolo; Mangues, Ramón; Villaverde, Antonio; et al.
Graphical abstract: Abstract: Nanostructured protein materials show exciting biomedical applications, since both structure and function can be genetically programmed. In particular, self-assembling histidine-rich proteins benefit from functional plasticity that allows the generation of protein-only nanoparticles for cell targeted drug delivery. However, the rational development of constructs with improved functions is limited by a poor control of the oligomerization process. By exploring cross-interactions between histidine-tagged building blocks, we have identified a critical architectonic role of divalent cations. The obtained data instruct about how histidine-rich protein materials can be assembled, disassembled and reassembled within the nanoscale through the stoichiometric manipulation of divalent ions, in a biochemical approach to biomaterials design. Statement of Significance: Divalent metal and non-metal cations such as Ni 2+, Cu 2+ Ca 2+ and Zn 2+ have been identified as unexpected molecular tools to control the assembling, disassembling and reassembling of histidine-rich protein materials at the nanoscale. Their stoichiometric manipulation allows generating defined protein-protein cross-molecular contacts between building blocks, for a powerful nano-biochemical manipulation of the material's architecture.